Ciclos de Formação Humana com Complexos de Estudo: implementação na Escola Municipal do Campo Zumbi dos Palmares - Rodrigues, Edinéia Karina (2020)
The theme of this study includes education in the field, within the Landless Rural Workers Movement (MST), with focus on the Pedagogical Proposal. The intention is to analyze the process of execution of the Pedagogical Proposal of the Human Training Cycle with Study Complexes, started on 2013, at the Campo Zumbi dos Palmares Municipal School, at Cascavel-PR. With the reference to historical-dialectic materialism, doing use of bibliographic research, the path of analysis first demarcates some counter-hegemonic currents with an approach to Anarchism, Paulo Freire, Historical-Critical Pedagogy of the MST, whose perspective is the human emancipation, centered on work as the activity that produces the life, opposing the neo-liberal capitalist model; follows the Russian Revolution and Educational; the MST’s concept of education and its Pedagogy, until the formulation of the Pedagogical Proposal of the Human Formation with Study Complexes, which resizes the form school, relating work to the lives of students, having the foundations of sciences, art, culture and technologies forged by the human being to the throughout history, linked to self-organization. The execution process of the Pedagogical Proposal in the School researched came from a history about Cascavel, a conflict territory, whose economy is driven by the agribusiness and, contradictorily that the MST was founded there; then, there is a history of Campo Zumbi dos Palmares Municipal School and the process of implementation of the Pedagogical Proposal researched. The methodological procedures are composed by the articulation of documentary research and semi-structures interviews with educators who work pedagogically with the students, thus defined in order to represent the School living reality. The results indicate the collective endeavor of the educators together with the school community on the execution of the Pedagogical Proposal. It’s worth mentioning the increase in the Educational Plan of the initial years of elementary school, the inclusion of Youth and Adult Education and Special Education. It appears a different reality, because it’s a municipal school, linked to the Municipal Education System of Cascavel, which has its own curriculum. It’s clear, on the Schools’ reality the necessity of considering the contradictions, the tensions, the limits and the possibilities that reflects the glimpse with the education as a counterhegemonic practice from/to the working classes.